Water-Education as a Promoter of Education for Sustainable Development: Three Studies in Portuguese-Speaking African Countries - Leitão, Mafalda Franco; Cunha, Albino; Ferreira, Manuela Malheiro (European Journal of Sustainable Development, 2020)
The present study is based on research in teacher self-training in Education for Sustainable Development (Leitão, 2012). Water was the motivating theme. The priority of a fair distribution of water, guaranteeing the consumption, in quality and quantity, to all mankind and living beings is urgent. To respond to water-related sustainability challenges, people worldwide need to acquire "water literacy" about various aspects of water use and management in order to ensure safer water consumption and to contribute to Disaster Risk Reduction (DRR). Three case studies were carried out in schools in three African countries: Angola, Guinea-Bissau and Mozambique. A model of skills in education for sustainable development was applied (Sleurs, 2008). From the analysis of these case studies the theoretical assumptions of research were strengthened by the effective professional practice. But, on contrary, the results that the pillars of sustainable development presented in the basic research should be reviewed, placing the political dimension as transversal, thus strengthening education for sustainable development as fundamental for critical and responsible citizens of the present and of the future. This experience paves the way for future water-education and education for sustainable development projects; such as the follow-up of these three schools. Keywords: Sustainable Development; Education for Sustainable Development; Water-education and Water Literacy; Case Study